APLIKASI METODE GEORADAR UNTUK IDENTIFIKASI STRUKTUR GEOLOGI DI JALAN HM. ARDAN RING ROAD 1 SAMARINDA - Syam, Ardian; Lepong, Piter; Supriyanto, Supriyanto (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2019)
Research has been conducted to find out the geological structure on jl. HM. Ardan, Ring Road 1, Samarinda, East Kalimantan. Using Ground Penetrating Radar (GPR) and radar reflection profiling techniques, this method is done by bringing the receiver and transmitter antenna ground simultaneously above level and then utilize the electromagnetic wave propagations for subsurface structures identification, which in this method produce a distance value and depth in the form of radar grams. Based on the results of this study can be identified Track 1 and 2 do not show the path of a geological structure on this track because only the process that resulted in the folding Landing dash that formed folding based on field control. On track 3, based on the reflection pattern, it can be estimated there is a lithological contact between the constituent materials, on track 4 it is estimated that there is a fault down at a depth of 1.6 m to 3 m, and from the reflection pattern can illustrate the lithological contact between constituent rocks. on track 5 and track 6 there is a shallow fault and is estimated based on the diffraction pattern recorded there is a water channel at the end of the track.